Development of battery impedance tester - Mohd Shahir, Mohd Sarif (2012)
Introduces an applicable method for measuring battery's internal impedance and conductance techniques have been advocated in the determination of the condition of lead-acid batteries in service. The battery itself has an internal resistance that makes it difficult to control the charging and discharging process because the capacity of the battery is estimated by the potential difference between the two electrodes of the battery, named external voltage. The usefulness of these "ohmic" techniques lies in an understanding of the bounds and domain of the measurement. Impedance model contains a lot of information that can indicate performance of battery. Therefore, establishment of accurate impedance model is very important. The impedance behaviour during individual discharge cycles as well as over its cycle life is obtained. Frequency response and battery impedance behaviour generally observed for a of commercially available batteries. The impedance is calculated by the ratio of voltage and current variation.